LDII Kabupaten Pati: Sejarah, Perkembangan dan Tokohnya - edy, edy supratno; Surasiyanto (Sekolah Tinggi Agama Islam Program Studi Sejarah dan Kebudayaan Islam, 2024)
This article discusses the history of the Pati Regency Indonesian Islamic Da'wah Institute (LDII) since this organization was named Islam Djamaah in 1970. Using historical methods, this article explores and presents facts about the history of its establishment, the model of da'wah and the challenges faced by KH. Muslih, a figure who pioneered the LDII Pati organization. After having experienced various obstacles and obstacles in the field, the successors of KH. Muslih, like KH. Anwar Muhammadin, SH., Drs. Djuwadi, Drs. Agus Priyono, KH. Nasrallah, and Drs. Sundoro succeeded in convincing the public that this organization was not a threat to society or the state. With a strategy of embracing other parties, LDII Pati held several national seminars that presented officials. Until 2023, LDII Pati already has a management structure of 16 branch heads (PC) and 39 sub branch heads (PAC).